Lack of Significant Effects of Glyphosate on Glyphosate-Resistant Maize in Different Field Locations - Bidóia, Vitor Simionato [UNESP]; Neto, José Cristimiano dos Santos; Maciel, Cleber Daniel de Goes; Tropaldi, Leandro [UNESP]; Carbonari, Caio Antonio [UNESP]; Duke, Stephen Oscar; Carvalho, Leonardo Bianco de [UNESP] (MDPI, 2023)
Glyphosate-resistant (GR) maize is dominant in countries where it is grown. Significant, adverse effects of glyphosate application to GR maize have been reported, but few data from robust studies exist to determine if such effects are common. In this study, the effects of recommended application rates (single and sequential applications) were used on GR maize grown at two locations for one season and for two seasons in a third location. No significant effects of glyphosate on mineral content (N, P, K, Ca, Mg, S, Cu, Fe, Mn, and Zn) in leaves or grain, plant height, stem diameter, ear parameters, or yield were found at any location or in any growing season. Likewise, harvested grain quality, as determined by percent starch, protein, and total lipids, was unaffected by glyphosate treatment at any location. Neither glyphosate nor aminomethylphosphonic acid, the primary degradation product of glyphosate, were found in grain from any treatment at any location, except for 20 ng g−1 of glyphosate found in grain from one season at one location. These results support the view that recommended applications of glyphosate have no significant effects on growth, grain composition, mineral content, grain quality, nor yield of GR maize.
Keywords: aminomethylphosphonic acid; glyphosate; herbicide; maize; mineral nutrition; seed quality; transgenic crop; yield; Zea mays